2016
DOI: 10.1158/1055-9965.epi-15-0406
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Exercise on the Insulin-like Growth Factor Axis in Oncology: Physiological Basis, Current, and Future Perspectives

Abstract: Exercise and physical activity have been shown to reduce the risk of many common cancers and strongly influence tumor biology. A cause-effect mechanism explaining this relationship is dependent on cellular pathways that can influence tumor growth and are exercise responsive. The insulin-like growth factor (IGF) axis is reported to promote the development and progression of carcinomas through cellular signaling in cancerous tissues. This review summarizes the physiologic basis of the role of the IGF axis in onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…The effect sizes were, however, very small and after adjustment for BMI, only the association with sedentary time in premenopausal women remained significant. Likewise, many studies reported nonsignificant findings 14,36,41 although some found a positive association. 50 Overall, our study confirms that the associations of physical activity and sedentary time with the IGF-I concentration are negligible, particularly after adjustment for BMI.…”
Section: Physical Activity and Sedentary Timementioning
confidence: 99%
See 1 more Smart Citation
“…The effect sizes were, however, very small and after adjustment for BMI, only the association with sedentary time in premenopausal women remained significant. Likewise, many studies reported nonsignificant findings 14,36,41 although some found a positive association. 50 Overall, our study confirms that the associations of physical activity and sedentary time with the IGF-I concentration are negligible, particularly after adjustment for BMI.…”
Section: Physical Activity and Sedentary Timementioning
confidence: 99%
“…Obesity and physical activity have been reported to influence circulating sex hormones and growth factors. [14][15][16][17] However, the evidence to date is not conclusive, particularly in premenopausal women due to small sample size as well as the cyclic nature of hormonal fluctuations before menopause. Given that the proliferative rate of mammary epithelial cells is highest in the mid-luteal phase, 18 menstrual cycle-specific analyses may provide insights into how obesity and physical activity influence the risk of premenopausal breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…First, exercise may suppress the development and proliferation of HCC through modulation of insulin-like growth factor 1 signal. Insulin-like growth factor 1 concentration is related to an increase in tumor growth and development of colon cancer in in vivo and in vitro studies (40). Exercise improves insulin resistance and decreases levels of insulin-like growth factor 1 in patients with breast cancer (39).…”
Section: Referencementioning
confidence: 99%
“…Higher serum IGFBP-3 is associated with a lower risk of developing advanced-stage prostate cancer [53]. However, while PRT has been shown to reduce plasma IGF-1 [103] and increase IGFBP-3 [114] levels in prostate cancer, current epidemiological studies in cancer populations show significant heterogeneity in the response of the systemic IGF axis to exercise [118]. This discrepancy may be attributed to baseline concentrations of the IGF ligands, as Nishida et al [119] showed that participants with elevated baseline IGF-1 experienced the greatest decrease in response to exercise.…”
Section: Metabolic Effectsmentioning
confidence: 99%
“…This discrepancy may be attributed to baseline concentrations of the IGF ligands, as Nishida et al [119] showed that participants with elevated baseline IGF-1 experienced the greatest decrease in response to exercise. Furthermore, there are current limitations in oncological research regarding the exercise response of autocrine, as compared to systemic IGF-1 [118]. In older adults with rheumatoid arthritis, PRT increased total lean and appendicular muscle mass, which was associated with increases in muscular IGF-1 and IGFBP-3 with no changes in systemic levels [120].…”
Section: Metabolic Effectsmentioning
confidence: 99%